Nevertheless, She Resisted – Role of the Environment on Listeria monocytogenes Sensitivity to Nisin Treatment in a Laboratory Cheese Model - Henderson, L. O.; Erazo Flores, B. J.; Skeens, J.; Kent, D.; Murphy, S. I.; Wiedmann, M.; Guariglia-Oropeza, V. (Frontiers in Microbiology, 2020)
The growth of Listeria monocytogenes on refrigerated, ready-to-eat food products is a major health and economic concern. The natural antimicrobial nisin targets the bacterial cell wall and can be used to inhibit L. monocytogenes growth on cheese. Cell wall composition and structure, and therefore the efficacy of cell wall acting control strategies, can be severely affected by environmental and stress conditions. The goal of this study was to determine the effect of a range of pH and temperatures on the efficacy of nisin against several strains of L. monocytogenes in a lab-scale, cheese model. Cheese was made with or without the addition of nisin at different pH and then inoculated with L. monocytogenes; L. monocytogenes numbers were quantified after 1, 7, and 14 days of incubation at 6, 14, or 22°C. While our data show that nisin treatment is able to reduce L. monocytogenes numbers, at least initially, growth of this pathogen can occur even in the presence of nisin, especially when cheese is stored at higher temperatures. Several environmental factors were found to affect nisin efficacy against L. monocytogenes. For example, nisin is more effective when cheese is stored at lower temperatures. Nisin is also more effective when cheese is made at higher pH (6 and 6.5), compared to cheese made at pH 5.5, and this effect is at least partially due to the activity of cell envelope modification genes dltA and mprF. Serotype was also found to affect nisin efficacy against L. monocytogenes; serotype 4b strains showed lower susceptibility to nisin treatment compared to serotype 1/2 strains. Overall, our results highlight the importance of considering environmental conditions specific to a food matrix when developing and applying nisin-based intervention strategies against L. monocytogenes.